PEMBINAAN KERUKUNAN HIDUP ANTAR UMAT BERAGAMA PASCA-KONFLIK TAHUN 1999 DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (STUDI DI KOTA AMBON PROVINSI MALUKU) - John E. de Fretes (Universitas Gadjah Mada, 2013)
This paper explained the dynamic of interreligious harmony establishment post 1999 conflict and its implication on below par regional resilience in Ambon. The qualitative data showed four obstacle factors of interreligious harmony, namely blasphemy, narrow primordial, religious deviation activity, and population dense which obstructed the interreligious establishment of pella-gandong. The Concept application of “agree in disagreement” and establishment of the four pillars were embodied in: (1) interreligious harmony legislation’s socialization; (2) community’s solidarity; (3) religious and government leaders’ exemplary, and (4) interreligious dialogue pillar. These would be implied on strong regional resilience in Ambon.Keywords: Harmony, Interreligious, Confl ict, and Regional Resilience.